Bearing Capacity Analysis and Zoning of Kathmandu for Shallow Foundations - Danai, Ram Krishna; Acharya, Indra Prasad (Journal of Advanced College of Engineering and Management, 2018)
The bearing capacity of foundation is the primary concern in the field of geotechnical engineering. In this study numerical models are developed for each of the secondary borehole data collected around Kathmandu valley. Finite element analysis (i.e. PLAXIS 2D) is carried out using Mohr-coulomb failure criteria to represent two dimensional soil models. Foundation is aimed to model as square footing and prescribed settlement of 10% of footing width is provided to obtain corresponding bearing capacity. In plaxis, effective stress is considered as an ultimate bearing capacity. Drained behavior with axisymmetical models have been considered for soil model in plaxis software. Various soil parameters like C (Cohesion), γ (unit weight), Φ (Frictional angle), ν (Poison ratio), E (Elasticity) for each 1.5m and 3m depths have been considered in models and in theoretical approaches.